ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERUBAHAN ALOKASI BELANJA MODAL (Studi Empiris Pada Kabupaten/Kota Jawa Timur Tahun 2018-2019) - Meltia Meltia; Moh. Amin; Hariri Hariri (e_Jurnal Ilmiah Riset Akuntansi, 2021)
This study aims to provide empirical evidence regarding the effect of Regional Original Income, Remaining Budget Financing, General Allocation Funds, Special Allocation Funds, and Profit Sharing Funds on Capital Expenditures for the regency / city of East Java. The sample in this study was the realization of the East Java district / city APBD during 2018-2019 which was published through the official website of the Directorate General of Fiscal Balance (DJPK). Sampling in this study is using purposive sampling method while the data analysis techniques used in this research are descriptive statistical test, normality test, classical assumption test, multiple linear regression analysis, and hypithesis test with a significant level (α) 0.005. The results of this study indicate that the Regional Original Income (PAD), the General Allocation Fund (DAU), the Revenue Sharing Fund (DBH) have a positive and significant effect on capital expenditure. Meanwhile, the Special Allocation Fund (DAK) and the excess of SiLPA Budget Financing have no effect on capital expenditures.Keywords: Local Own Revenue (PAD), Remaining Budget Financing (SiLPA), General Allocation Funds (DAU), Special Allocation Funds (DAK), Profit Sharing Funds (DBH), and Capital Expenditures.